Kajian Teologis Tentang Tribulasi dan Maknanya Bagi Orang Percaya - Yusni Telaumbanua (STIKAS Santo Yohanes Salib Kalimantan Barat, 2024)
Tribulation is a significant theme in Christian theology, referring to the suffering and hardships experienced by believers leading up to the second coming of Christ. This study aims to analyze the theological understanding of tribulation and explore its meaning for the lives of believers. The main issue addressed is how tribulation is understood in biblical perspective and its relevance to strengthening the faith of Christians in the modern era. The research method employed is a qualitative approach with literature review, examining biblical texts and theological works discussing tribulation. The findings show that tribulation is viewed as a test of faith that serves to strengthen the spirituality of believers, though there are various interpretations regarding its duration and intensity. The discussion also reveals differences in views among premillennialism, amillennialism, and postmillennialism in interpreting tribulation. In conclusion, tribulation plays a vital role in the lives of believers as a trial that leads to spiritual growth and hope for the second coming of Christ. A deeper understanding of tribulation can provide spiritual resilience for Christians amidst the increasing challenges of the modern world.